PEMILIHAN MEDIA KOMUNIKASI DARI MAHASISWA UNIVERSITAS BUNDA MULIA ANGKATAN 2010/2011 JURUSAN MANAJEMEN - Lelly Christin (Universitas Bunda Mulia, 2017)
Lately competition becomes really tough, because of that each University has to choose the right strategy in order to increase their market share. Some of the strategies than can be done are by choosing the right communication media for each promotion that the university wants to do. For the reason, this research wants to know which communication media that really attracts students at Bunda Mulia University, Management Major in year 2010/2011. In this research, the writers used incidental sampling. The writers also use questionnaire for gathering the data or information need. To analyze the data, the writes use SPSS ver. 15.0 for windows. The conclusion of this research about the highest percentage to the lowest percentage of the most attractive communication media are television, internet, direct mail, magazines, radio, newspapers, outdor advertising, and the last one is telemarketing. According to result, the highest percentage of an attractive communication media is television, so writer suggest that the best media to do the promotion is television media.Keyword :Communication media, markeing communication, integrated marketing communication